The appropriateness and usefulness of accrual accounting in public sector environment / Herni Rahmat - Rahmat, Herni (2014)
The transformation from cash basis accounting to accrual-based accounting in financial reporting of public sector is expected to increase public accountability of public managers. However, the suitability of accrual-based accounting in the public sector are debatable based on the experience of pioneer countries of accruals. This study explores the perceptions of Malaysian public managers on the applicability of accrual accounting concept in the public sector and the usefulness of accrual-based governmental financial reports towards the public managers in discharging their duties. Besides, this study also highlights the neutral response upon the study. This study finds that there are significant differences between the responses from three different level of government sector on the reporting entity of a consolidated report, the definition and concept of controlled assets by public entities and the use of accumulated surplus and equity as a financial performance indicator. In addition, the study indicates that familiarity and experience over time will contribute to higher perceptions towards the usefulness of accrual-based information. Furthermore, the neutral response from the respondents suggests that an in-depth discussion between the public sector managers and experts from the accounting field to improve the understanding among the Malaysian public sector managers. Hence, this study provides useful insights to the standard setters in the process of MPSAS formulation with regards to the general purpose financial reporting model for the public sector in Malaysia. In addition, it will improve the public accountability practice in Malaysian governmental financial reporting.